Stability of Four New Sources of Bacterial Leaf Blight Resistance in Thailand Obtained from Indigenous Rice Varieties - Sribunrueang, Arthit; Chankaew, Sompong; Thummabenjapone, Petcharat; Sanitchon, Jirawat (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most serious diseases in rice production. Breeding varieties specifically for their resistance to BLB disease is therefore an efficient and cost-effective strategy. However, the resistance gene for BLB can be race and non-race specific, meaning it is often overcome by the pathogen. The identification of new sources of resistance genes for Xoo is crucial in rice breeding programmes. In this study, six rice varieties were assessed using six Xoo isolates in multiple screening conditions. The GGE biplot analysis considers both genotype (G) and genotype environment (GE) interaction effects and demonstrates GE interaction. The first two principal components (PCs) accounted for 95.46% of the total GE variation in the data. Based on lesion length and stability performance, Phaladum was the most ideal genotype against all Xoo isolates in the four screening conditions. The results relayed that Phaladum indigenous rice varieties could be considered as new sources of bacterial leaf blight resistance in Thailand. In the future, the BLB resistance gene in this variety will be identified in regard to mode of inheritance and used as parental line in rice breeding programmes for resistance to BLB.